Self-stabilizing dielectric elastomer generators. (13th February 2017) - Zanini, P; Rossiter, J; Homer, M
Abstract: Dielectric elastomer generators (DEGs) are an emerging technology for the conversion of mechanical into electrical energy. Despite many advantageous characteristics, there are still issues to overcome, including the need for charging at every cycle to produce an electrical output. Self-priming circuits (SPCs) are one possible solution, storing part of the electric energy output of one cycle to supply as input for the next, producing a voltage boost effect. Until now, studies regarding SPCs neglect to consider how the increasing voltage will create an electromechanical response and affect the DEG when driven by an oscillatory mechanical load. In the present work we model this force-based actuation, including coupling between the DEG and SPC, in order to predict the dynamics of the system. In such cases, the DEG has a mechanical response when charged (actuator behaviour), and as the voltage increases, this actuation-like effect increases the capacitance values that bound the cycle. We show how this inherent nonlinearity yields a reduction in the DEG's capacitance swing and reduces the performance of the SPC, but also self-stabilizes the system. This stability is useful in the design of robust DEG energy harvesters that can operate near to, but not enter, failure mode.